Climate change and infrastructure investment in developing countries: The case of Mozambique - Channing Arndt; Paul Chinowsky; Kenneth Strzepek; James Thurlow (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
Climate change may damage road infrastructure to the potential detriment of economic growth, particularly in developing countries. To quantitatively assess climate change's consequences, we construct a climate-infrastructure model based on stressor-response relationships and link this to a recursive dynamic economy-wide modelto estimate and compare road damages to other climate change impact channels. We apply this framework to Mozambiqueand simulate four future climate scenarios. Our results indicate that climate change through 2050 is likely to place a drag on economic growth and development prospects. The economic implications of climate change appear to become more pronounced from about 2030. Nevertheless, the implications are not so strong as to drastically diminish development prospects. An adaptation policy of gradual evolution towards road designs that accommodate higher temperatures and follows rainfall trends (wetter or dryer) improves outcomes. At the same time, a generalized policy of upgrading all roads does not appear to be merited at this time. Our findings suggest that impact assessments should include the damages on long-run assets, such as infrastructure, imposed by climate change.
Keywords: Q54; O44; O55; 330; climate change; infrastructure vulnerability; productivity; economic growth; Mozambique; Klimawandel; Infrastrukturinvestition; Wirtschaftswachstum; Mosambik